Over 11,000 households benefit from bamboo bioenergy across Africa and Indonesia, via support from the International Network for Bamboo and Rattan (INBAR) for women-led bamboo enterprises, sustainable livelihoods, and land restoration - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The International Network for Bamboo and Rattan (INBAR) in close collaboration with FTA partners led and transferred research on bamboo bioenergy production technologies and smallholder bamboo value chains across Africa and Asia. Related projects raised awareness and influenced households to plant bamboo on farms and degraded lands to improve rural livelihoods, targeting women and youth. Adoption of bamboo-planting across Africa and Southeast Asian countries is expected to decrease deforestation and support land restoration.